ETIKA KOLABORASI DAN DISKRESI ANTAR TENAGA MEDIS DALAM PELAYANAN KESEHATAN BERBASIS TIM - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (Jurnal Kesehatan, 2025)
Team-based healthcare requires strong ethical collaboration and discretion among healthcare professionals to ensure patient quality and safety. Effective interprofessional collaboration is built through open communication, mutual respect, clarity of roles, and shared responsibility among healthcare professions. However, practices in the field often face challenges such as differences in competence, professional hierarchy, communication barriers, and resource limitations. Discretion in the delegation of authority among healthcare professionals is a critical aspect that must be carried out ethically, taking into account legal boundaries, competencies, and applicable operational standards. This literature review emphasises that the proper application of principles of collaborative ethics and discretion can improve the quality of care, strengthen professional relationships, and create a harmonious and safe work environment for patients. Sustained efforts in interprofessional education, regulatory strengthening, and the development of a collaborative work culture are key to maintaining ethical collaboration in healthcare settings.